IFNAR2 Deficiency Causing Dysregulation of NK Cell Functions and Presenting With Hemophagocytic Lymphohistiocytosis - Passarelli, Chiara; Civino, Adele; Rossi, Marianna N.; Cifaldi, Loredana; Lanari, Valentina; Moneta, Gian Marco; Caiello, Ivan; Bracaglia, Claudia; Montinaro, Raffaele; Novelli, Antonio; De Benedetti, Fabrizio; Prencipe, Giusi (Frontiers in Genetics, 2020)
We describe a 2 years boy with two previously undescribed frameshift mutations in the interferon (IFN)α/β receptor 2 (IFNAR2) gene presenting with hemophagocytic lymphohistiocytosis (HLH) following measles-mumps-rubella vaccination. Functional analyses show the absence of response to type I IFN in the patient’s cells, as revealed by lack of phosphorylation of STAT1 and lack of induction of interferon-stimulated genes upon ex vivo stimulation with IFNα. HLH has been reported in patients with inborn errors of type I IFN-mediated immune responses following vaccination with live-attenuated viruses. The relation between HLH and defective type I IFN-mediated responses is unclear. We show that in patient’s natural killer (NK) cells stimulated with IFNα the expected increase in degranulation and inhibition of IFNγ production were affected. These data support a role for NK cell function dysregulation and lack of inhibition of IFNγ production as contributors to the development of HLH in patients with impaired type I IFN signalling.